Frequency of Color Blindness in Pre-Employment Screening among Recruits for Defense Persons in Geewan Recruiting Centre, Kuwait - Sultana, Tahmina; Jesmin Sultana, Jannat Jahan; Chokder, Mohammad Sadikul Islam; Hossain, Muhammad Kamal (Journal of Armed Forces Medical College, Bangladesh, 2026)
Background: Color blindness or Color Vision Deficiency (CVD) is X-linked recessive disorder characterized by a decreased ability to perceive the difference between colors. Objective: To determine the prevalence rate of color blindness among candidates for new police and military recruits in Kuwait. Methods: A cross-sectional descriptive review of the medical records of 10,000 young male adults (Kuwait has only males in their uniformed officials) who were screened and examined for police and military service between December 2021 and August 2022 was conducted. Ishihara color test plates were used to diagnose color blindness among participants. The findings were divided into two groups. Data were tabulated, and statistically analyzed. The prevalence of color blindness among the new candidates was determined. Results: A total of 10,000 young male adults (As no Uniformed Female is allowed in Kuwait Army) were examined. Among the studied sample, 370(3.7%) out of 10000 were unfit for defense service due to color blindness, with a mean age of 21.7±.39 SD years (range 17-26 years). The prevalence of blindness was found to be 3.7% (2.5-4.9). Conclusion: The prevalence of color blindness among male young recruits was almost the same compared with other studies in neighboring countries and around the world. JAFMC Bangladesh, Vol 21, No 2 (December) 2025:26-28